Lecturers' Perspective of E-Counseling Service During Online Learning - Asriyanti Rosmalina (AL-ISHLAH: Jurnal Pendidikan, 2023)
The goal of this study was to find out what the lecturers thought about e-counseling services in online learning. The difference between this research and previous research can be seen in how lecturers understand e-counselling. As a counsellor in the classroom, the lecturer must have professional knowledge about their role in the classroom. This study took a qualitative approach and used descriptive methods. Thirty lecturers from a State Islamic Institute in Cirebon took part in the study. When sampling, purposeful sampling was used. Data were collected using observation techniques, documents and questionnaires. The stages of data analysis are data reduction, data presentation, and drawing a conclusion. The results showed that the lecturers' attitudes towards e-counselling in online learning were positive. A lecturer in the class helps students understand the material and acts as a counsellor inside and outside of the classroom to help students who are having trouble learning. The results of this study have implications for and help higher education institutions improve the role of teachers in the classroom as both learning facilitators and counsellors, the quality of mastering digital technology, and understanding how to help students.